2017
DOI: 10.25011/cim.v40i2.28194
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of vascular endothelial growth factor in patients with renal cell carcinoma: a systematic review of the literature and meta-analysis

Abstract: Objective: Vascular endothelial growth factor (VEGF) serum level or tumor expression may be prognostic in renal cell carcinoma (RCC). The purpose of this meta-analysis was to examine the prognostic value of serum VEGF level and tumor expression in patients with RCC.Methods: PubMed and EMBASE databases were searched until September 26, 2016. Prospective and retrospective studies of RCC patients that had VEGF levels measured were included. Outcome measures were overall survival (OS), disease-specific survival (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Several clinical trials combining ICIs with Bevacizumab are also ongoing in mRCC ( Table 1 ), in which elevated serum and tumor VEGF levels have been associated with poor survival ( 249 ). In a study combining Bevacizumab with Atezolizumab, the authors demonstrated the ability of Bevacizumab to induce a Th1 signature with chemokines involved in lymphocyte trafficking, tumor MHC I protein expression and infiltration of tumor-specific T cell clones.…”
Section: Combination Strategies For Improving Ici Therapy By Targetinmentioning
confidence: 99%
“…Several clinical trials combining ICIs with Bevacizumab are also ongoing in mRCC ( Table 1 ), in which elevated serum and tumor VEGF levels have been associated with poor survival ( 249 ). In a study combining Bevacizumab with Atezolizumab, the authors demonstrated the ability of Bevacizumab to induce a Th1 signature with chemokines involved in lymphocyte trafficking, tumor MHC I protein expression and infiltration of tumor-specific T cell clones.…”
Section: Combination Strategies For Improving Ici Therapy By Targetinmentioning
confidence: 99%
“…They showed that the level of VEGF is inversely correlated with the levels of Alb and NLR. In a meta-analysis, Shen et al showed that elevated serum VEGF level is associated with worse OS, disease specific survival (DSS) and PFS in patients with RCC (28).…”
Section: Figure 1 Progression-free Survival (Pfs) In Renal Cell Carci...mentioning
confidence: 99%
“…There is a broad sense that tumor immune evasion closely relates to angiogenesis, and, in turn, tumor angiogenesis highly depends on immunosuppressive microenvironment, which is companion processes in tumorigenesis ( Figure 2 ) ( 40 ). Mounting evidence now show that elevated level of VEGF in tumor lesion may cause suppression in both innate and adaptive immune response, and increased serum or tumor VEGF levels are associated with unfavorable prognosis in mRCC patients ( 41 ). Reportedly, VEGF can inhibit the innate immune system via hampering the transcriptional program required for maturation of DCs, the critical cells in immune activation, and increasing the presence of MDSCs, which represent a heterogeneous population of cells that accumulate in tumor-bearing hosts, characteristic by their potent immune-suppressive activity against cytotoxic tumor-infiltrating lymphocytes (TIL) ( 42 45 ).…”
Section: Biological Rationale For Combined Aa and Immune-activating Tmentioning
confidence: 99%